Teachers' Profile, Knowledge Competence, and Skill Competence in Laboratory Instruction; Its Implications to Physics Teaching - Atud, Florence Mae R.; Cabrera, Rhea M.; Calzada, Marc Paul T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Effective science instruction requires more than just dispensing information and conceptual knowledge; science teachers also need to have in-depth knowledge, understanding, and abilities to give their students appropriate and pertinent scientific tasks. Despite the fact that teachers exhibit proficiency in laboratory instruction, more research is required to determine how this proficiency directly impacts student learning outcomes in lab environments. Hence, a descriptive-correlational research approach was conducted to determine the relationship between the profile of science teachers and their knowledge and skill competence in science laboratory instruction. Results revealed that gender (sex) has a negative correlation with both knowledge and skill competency. This indicates that male and female teachers may have different competency levels. Moreover, higher degrees and teachers’ field of specialization contribute positively to both knowledge and skill competency in science laboratory instruction. However, teaching position and length of teaching have weak indicating that experience alone may not strongly influence knowledge and skill competence in science laboratory.